2002
DOI: 10.1017/s0022050702000529
|View full text |Cite
|
Sign up to set email alerts
|

Real Inequality in Europe Since 1500

Abstract: , seminar participants at Arild and Davis, and the referees for helpful suggestions. 1 Rousseau, Les Confessions, book 6 (a quip later attributed, falsely, to Marie Antoinette). 2 A direct predecessor to this study is Kula, Economic Theory, pp. 119-31. In Kula's pioneering exercise, we see the first good sketch of the importance of differences in cost-of-living movements, though without any link-up with income measures and with some limitations of commodity coverage and geographic coverage. Kula offered styliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
59
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(65 citation statements)
references
References 48 publications
2
59
0
4
Order By: Relevance
“…In addition, this divergence was even greater in real than in nominal terms, because luxuries became much cheaper relative to staples (van Zanden 1995;Hoffman et al 2000;Pamuk 2000). While we still lack estimates or even guesstimates on the world distribution of income between 1500 and 1820, the bits and pieces we do have suggest unambiguously that global inequality must have risen significantly in this pre-industrial era.…”
Section: Global Divergence Is Far Older Than Globalizationmentioning
confidence: 99%
“…In addition, this divergence was even greater in real than in nominal terms, because luxuries became much cheaper relative to staples (van Zanden 1995;Hoffman et al 2000;Pamuk 2000). While we still lack estimates or even guesstimates on the world distribution of income between 1500 and 1820, the bits and pieces we do have suggest unambiguously that global inequality must have risen significantly in this pre-industrial era.…”
Section: Global Divergence Is Far Older Than Globalizationmentioning
confidence: 99%
“…It claims that what drove distributional alterations were supervening modifications in the 26 Practically every study in this field has concluded in a similar vein. Hoffman et al (2002) find that: 'inequality within the nations of western Europe has risen greatly' (p. 324). This is echoed by Van Zanden (1995): 'a super Kuznets curve spanning many centuries […] was characterized by rising inequality' (p. 662).…”
mentioning
confidence: 99%
“…"Farm Settlement with Imperfect Capital Markets: A Life-Cycle Application to Upper Canada, 1826-1851", Canadian Journal of Economics,Vol.34,No.1, Ibid,p.177. 121 The best known paper is that of Philip Hoffman, David S. Jacks, Patricia Levin and Peter Lindert. 2002.…”
mentioning
confidence: 99%